Effective Generation of Glucosylpiericidins with Selective Cytotoxicities and Insights into Their Biosynthesis - Liu, Zengzhi (Appl Environ Microbiol, 2021)
Exploring unknown glycosyltransferases (GTs) is important for compound structural glycodiversification during the search for drug candidates. Piericidin glycosides have been reported to have potent bioactivities; however, the GT responsible for piericidin glucosylation remains unknown. Herein, BmmGT1, a macrolide GT with broad substrate selectivity and isolated from Bacillus methylotrophicus B-9987, was found to be able to glucosylate piericidin A1 in vitro. Next, the codon-optimized GT gene sbmGT1, which was designed based on BmmGT1, was heterologously expressed in the piericidin producer Streptomyces youssoufiensis OUC6819. Piericidin glycosides thus significantly accumulated, leading to the identification of four new glucopiericidins (compounds 3, 4, 6, and 7). Furthermore, using BmmGT1 as the probe, GT1507 was identified in the genome of S. youssoufiensis OUC6819 and demonstrated to be associated with piericidin glucosylation; the overexpression of this gene led to the identification of another new piericidin glycoside, N-acetylglucosamine-piericidin (compound 8). Compounds 4, 7, and 8 displayed cytotoxic selectivity toward A549, A375, HCT-116, and HT-29 solid cancer cell lines compared to the THP-1 lymphoma cell line. Moreover, database mining of GT1507 homologs revealed their wide distribution in bacteria, mainly in those belonging to the high-GC Gram-positive and Firmicutes clades, thus representing the potential for identification of novel tool enzymes for compound glycodiversification. IMPORTANCE Numerous bioactive natural products are appended with sugar moieties and are often critical for their bioactivities. Glycosyltransferases (GTs) are powerful tools for the glycodiversification of natural products. Although piericidin glycosides display potent bioactivities, the GT involved in glucosylation is unclear. In this study, five new piericidin glycosides (compounds 3, 4, 6, 7, and 8) were generated following the overexpression of GT-coding genes in a piericidin producer. Three of them (compounds 4, 7, and 8) displayed cytotoxic selectivity. Notably, GT1507 was demonstrated to be related to piericidin glucosylation in vivo. Furthermore, mining of GT1507 homologs from the GenBank database revealed their wide distribution across numerous bacteria. Our findings would greatly facilitate the exploration of GTs to glycodiversify small molecules in the search for drug candidates.